Karakteristik Permukiman Kumuh di RW 04, Kelurahan Manggarai, Kecamatan Tebet, Jakarta Selatan - Azqia, Mutiara Nur; Jalaluddin, Muzani; Handawati, Rayuna (P4W IPB, 2025)
This study aims to analyze the characteristics of slum settlements in RW 04 Kelurahan Manggarai, Tebet District, South Jakarta. The research method used is descriptive quantitative with purposive sampling technique. The population in this study is the residents of RW 04 Kelurahan Manggarai, with a total population of 2,648 individuals. From this population, a sample of 348 individuals was taken. Data collection techniques include distributing questionnaires, literature study, and using internet sources. The study found that the settlements in RW 04 Kelurahan Manggarai are categorized as moderately slum. The characteristics of these settlements include very high population density, with the majority of house or land ownership being inherited or family-owned houses. The common type of buildings are duplex houses, with house walls made of wood or planks, and house floors made of cement. Land use is dominated by irregular housing, and there is also the presence of industries, markets, warehouses, and transportation infrastructure in the area.